Level of readiness of employees of Systems Plus College Foundation (SPCF) on Disaster Risk-Reduction Management (DRRM) - Christian Jay S. Orte (Journal of the Pakistan Medical Association, 2024)
Objective:To determine the level of readiness on disaster risk-reduction management among employees of an educational institution. Method: The descriptive, evaluative study was conducted from March to April 2022 at 6 branches of Systems Plus College Foundation, Philippines, in Balibago, Rizal, Miranda, San Fernando, Caloocan and Cubao after approval from the ethics review committee of the Our Lady of Fatima University, Philippines, and comprised employees who were associated with the college for at least 6 months. Data was collected using Google Forms, and a validated tool was used to assess the disaster risk-reduction management readiness. The responses were categorised into 5 groups, ranging from ‘very much ready’ to ‘not ready’. Gathered data was analysed by using SPSS version 20. Mean results were derived and presented with standard deviation. Result: The responses suggested moderate readiness regarding structural safety codes 3.02±0.98, non-structural safety codes 3.02±1.04, availability of emergency supplies and equipment 2.84±1.09, and servicing and maintenance 2.85±1.03. Conclusion: Increasing the level of readiness related to disaster risk-reduction management must be given priority to ensure the safety of the employees in a higher education institution. Keywords: Advisory Committees, Risk Reduction, Disaster, Planning, Health facilities